Motivational Interviewing: Concept and Application in Persons with Chronic Kidney Disease - Tiansaard, Juthamas; Kanogsunthornrat, Nirobol (Nursing Research and Innovation Journal, 2017)
Abstract Persons with chronic kidney disease (CKD) need to adhere to numerous medical treatments and modify their behaviors and life-styles that are complex and difficult because of multiple system involvement. This article presents the concept and application of the motivational interviewing from literature reviews, authors’ experiences in the CKD clinic, and research results of applying this concept in persons with chronic diseases, particularly chronic kidney disease. This information is expected to be beneficial for advanced practice nurses (APNs) working as CKD clinical nurse specialists. Their important roles are to educate, promote, and support persons with CKD to achieve healthier behavior and better outcomes. Keywords: Motivational interviewing, Chronic kidney disease, Advanced practice nurses, Clinical nurse specialist